Villaovejuna a lo Llanero, Experiencia de una Maestra Artista en Formación (2024)
This work is part of the research group “Didactics of the performing arts” and contributes to the line of Pedagogy linked to the acts of creation. In particular, it addresses the experience lived during the creative process of the assembly of the work Villaovejuna, a free version of Fuenteovejuna by Lope de Vega, carried out during the second semester of 2022 in the courses of Medieval and Renaissance Theater and Llanera Dance of the Bachelor of Performing Arts at the Antonio Nariño University. Therefore, I have decided to collect and reflect on the experience lived in the assembly process, where the collective creation was guided by two teachers.